Weed Management Guide for Florida Lawns - Joseph Bryan Unruh; Ramon G. Leon; Barry J. Brecke; Laurie E. Trenholm (EDIS)
Weeds can be defined as unwanted plants or plants growing out of place. Proper identification and some understanding of how and why weeds are present in a lawn are important when selecting the best control strategy. Knowing whether or not weeds were previously present in a particular area also helps homeowners prepare control measures in the future. Weed control should be a carefully planned and coordinated program. This 8-page fact sheet was written by J. Bryan Unruh, Ramon G. Leon, Barry J. Brecke, and Laurie E. Trenholm, and published by the UF Department of Environmental Horticulture, July 2013.